Potential for reducing urban emissions with Semarang City pedestrian paths - Azizah Kirana Prasetya; Setiadji Bagus Hario; Huboyo Haryono Setiyo; Wijaya Arief Satya (E3S Web of Conferences)
Semarang City, as one of the big cities in Indonesia, faces significant challenges related to greenhouse gas (GHG) emissions, most of which come from the transportation sector. These emissions contribute to climate change and the decline in air quality in the city. This study explores the potential for reducing GHG emissions through the development of pedestrian paths in Semarang. By analyzing transportation emission data and the coverage of existing pedestrian paths, this study assesses the effectiveness of pedestrian path development in reducing emissions and improving urban quality of life. The methodology used includes GHG emission analysis, assessment of the area and coverage of pedestrian paths, and emission reduction projection models based on user survey data. Currently, only around 20% of the total roads in Semarang City have been built for pedestrian paths. By expanding and improving the quality of pedestrian paths, the potential for reducing CO2 emissions can reach 11% of total transportation emissions. This study suggests further development of pedestrian paths by considering factors such as comfort, accessibility, and connectivity to public transportation. This development not only has the potential to reduce GHG emissions but also increasing the resilience of cities to global climate change.